Sistem Pengendali Kualitas Air untuk Budidaya Ikan Guppy berdasarkan Suhu dan Derajat Keasaman Air menggunakan Metode KNN (K-Nearest Neighbor) - Rizky Widya Mahendra; Eko Setiawan; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Indonesia, which is an archipelagic country, is home to various types of fish, from edible fish to ornamental fish used to beautify a room. One of the most popular aquarium fish today is the guppy fish, so it's understandable that there are more and more guppy fish fans. Of course, currently guppy fish farming is a promising field of activity for current cultivators because of its high selling value. However, keeping guppy fish is not easy, because the quality of the water used in the guppy fish habitat must be maintained, otherwise the water quality will cause the fish to get sick. This condition can be caused because there are some cultivators who do not carry out routine maintenance for guppies. The most common mistakes are incorrect selection of the aquarium location which causes significant changes in water temperature, as well as improper water management which causes changes in water pH that are too high. So we need an automatic system that can control the condition of the water. By using the KNN (KNearest Neighbor) method, the accuracy value of K is obtained, the K value using K=3, K=5, and K=11 gets an accuracy value of 95%, while the K value using K=7 and K=9 accuracy of 100%, after KNN gets the results of the detection, these results will be useful for regulating the action of the actuator. The use of the system affects the development of guppies, for aquariums that use the system the growth of fish is faster than the aquarium that does not use the system..